Evidence for selection by male mating success in natural populations of Drosophila pseudoobscura. - Anderson, W W (1979)
Gene arrangement frequencies were determined at two stages in the life history of Drosophila pseudoobscura taken from nature. Three populations in the central highlands of Mexico were each sampled twice during 1976. Gene arrangement frequencies were measured in adult males and in larvae that were the offspring of females collected at the same time. The adult males were in all likelihood a representative sample of those who fathered the larvae produced by the wild females. Differences in gene arrangement frequency between these two life stages should indicate the operation of natural selection. One-third of our comparisons of common gene arrangement frequencies in males and in larvae from the next generation were statistically significant, as were one-third of our comparisons of total frequency arrays in the two life stages. We consider the components of selection that could produce such frequency changes and reason that male mating success must be the major one. Gene arrangement frequencies in the Mexican populations fluctuate within wide bounds. Selection must act to retain the polymorphism in the face of this flux in gene arrangement frequencies, and we suggest that male mating success plays an important role.